R534C mutation in hERG causes a trafficking defect in iPSC-derived cardiomyocytes from patients with type 2 long QT syndrome - Mesquita, Fernanda C. P. (2019)
Patient-specific cardiomyocytes obtained from induced pluripotent stem cells (CM-iPSC) offer unprecedented mechanistic insights in the study of inherited cardiac diseases. The objective of this work was to study a type 2 long QT syndrome (LQTS2)-associated mutation (c.1600C > T in KCNH2, p.R534C in hERG) in CM-iPSC. Peripheral blood mononuclear cells were isolated from two patients with the R534C mutation and iPSCs were generated. In addition, the same mutation was inserted in a control iPSC line by genome editing using CRISPR/Cas9. Cells expressed pluripotency markers and showed spontaneous differentiation into the three embryonic germ layers. Electrophysiology demonstrated that action potential duration (APD) of LQTS2 CM-iPSC was significantly longer than that of the control line, as well as the triangulation of the action potentials (AP), implying a longer duration of phase 3. Treatment with the IKr inhibitor E4031 only caused APD prolongation in the control line. Patch clamp showed a reduction of IKr on LQTS2 CM-iPSC compared to control, but channel activation was not significantly affected. Immunofluorescence for hERG demonstrated perinuclear staining in LQTS2 CM-iPSC. In conclusion, CM-iPSC recapitulated the LQTS2 phenotype and our findings suggest that the R534C mutation in KCNH2 leads to a channel trafficking defect to the plasma membrane.